الخبر فى كتب (التراجم) للصفدى: أنواعه وآليات بنائه - فاهم، شيماء خيري; جفات، أحمد على (جامعة القادسية - كلية التربية, 2016)
يهدف هذا البحث إلى التعرّض لدراسة جنس الخبر في كتب (التراجم) للصفدي، والتعرف على أنماط وآليات بناء هذا الجنس القصصي القصير الذي يغلب عليه قول الحقيقة ويشير إلى سرد شيء من التاريخ، فهو يمثل المصدر الرئيس للمعرفة والمادة الأساس في الرواية العربية، وقد اكتسب هذه السمة لأنه أصغر وحدة حكائية تؤدي وظيفة الإبلاغ. وتتكون هذه الدراسة من توطئة ومبحثين وخاتمة. القينا الضوء في التوطئة على مصطلح الخبر في اللغة والاصطلاح مع إعطاء نبذة عن ماهية جنس الخبر، وقد تكفّل المبحث الأوّل بالتعرّف على أنماط الخبر الواردة في كتب (التراجم) للصفدي، أما المبحث الثاني فقد اختص بدراسة آليات البناء الهيكلي للخبر في هذه الكتب، وكانت الخاتمة في عرض النتائج التي توصل إليها البحث خلال رحلته في هذه الكتب.
The “predicate” in AlSafdi’s books (AlTarajim), its sorts and constructing techniques Abstract This study aims to explore the sort of the “predicate” in AlSafdi’s books (Altarajim), and meet the manners and the techniques in constructing the short narrative sort, which is predominated by telling truth and narrate something of history. It represents the main source for knowledge and the raw material in Arabic novel. It gains this feature because it is the smallest unit of narrative that functions in telling. This study consists of introduction, two entries and a conclusion. Through the introduction, I shed light on the lexical meaning of the word “Predicate” as a term, in addition to giving a short summary about “predicate’s sort essence. The second entry introduces the “predicate” styles in in AlSafdi’s books (Altarajim). While the second entry studies the mechanisms of constructing the structure of the “Predicate” in the above mentioned set of books. The conclusion shows the results of the study.
Keywords: الخبر الأدبى -- الأجناس الأدبية -- كتب التراجم -- الصفدى